AGROINDUSTRI KERUPUK RAMBAK DI DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR PROPINSI RIAU (STUDI KASUS PADA USAHA KERUPUK “GMC”) - Tibrani Tibrani; Kasman Karimi (LPPM - STIE SAKTI ALAM KERINCI, 2023)
Small industry engaged in the agroindustry of rambak crackers of the type of rambak eats in Kampar Regency is in Pandau Jaya Village, Siak Hulu District, namely the small industry of “GMC” Rambak Crackers business. This business is the only agroindustry business that is developing quite well, has been operating for a long time, namely since 2011 until now. This study aims to analyze: 1) Entrepreneurial Characteristics and Business Profile of